2011
DOI: 10.1128/aac.01646-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Antivirulence Drug against Streptococcus mutans : Repression of Biofilm Formation, Acid Tolerance, and Competence by a Histidine Kinase Inhibitor, Walkmycin C

Abstract: Two-component signal transduction systems (TCSs) in prokaryotes often regulate gene clusters that induce pathogenicity, and thus they have frequently been proposed as potential drug targets for attenuating the virulence of pathogens. The pathogenic potential of Streptococcus mutans, the major etiological pathogen of dental caries, is also regulated by its TCSs. The object of this study was to evaluate the effect of a histidine kinase (HK) inhibitor against two major virulence factors of S. mutans: biofilm form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…During colonization of tooth surfaces, S. sanguinis interactions with dental pellicle, biofilm extracellular matrix, and/or coadherent microorganisms likely require dynamic cell surface fitting in response to host and microbial stimuli, a process that involves two-component regulatory systems. The TCS VicRK Sm of S. mutans, a competitor of S. sanguinis which promotes cariogenic biofilms, regulates biofilm formation and virulence (12), which raises interest in this TCS (also called WalRK) as a therapeutic target (34). In this study, we showed that VicRK Ss regulates critical functions necessary for S. sanguinis to initiate biofilms, including chain formation, tolerance to oxidative stress, production of hydrogen peroxide, and amounts of eDNA.…”
Section: Discussionmentioning
confidence: 79%
“…During colonization of tooth surfaces, S. sanguinis interactions with dental pellicle, biofilm extracellular matrix, and/or coadherent microorganisms likely require dynamic cell surface fitting in response to host and microbial stimuli, a process that involves two-component regulatory systems. The TCS VicRK Sm of S. mutans, a competitor of S. sanguinis which promotes cariogenic biofilms, regulates biofilm formation and virulence (12), which raises interest in this TCS (also called WalRK) as a therapeutic target (34). In this study, we showed that VicRK Ss regulates critical functions necessary for S. sanguinis to initiate biofilms, including chain formation, tolerance to oxidative stress, production of hydrogen peroxide, and amounts of eDNA.…”
Section: Discussionmentioning
confidence: 79%
“…Natural products and derivatives, such as green tea catechins (Hirasawa et al 2006), cranberry constituents , Galla chinensis (Xie et al 2008), citrus lemon oil (Liu et al 2013), mushroom extracts (Yano et al 2010), and several bioactive macromolecules (Shang et al 2014;Lee and Park 2015), have been reported to be effective against the growth and adherence of S. mutans. In addition, small molecules, such as tt-farnesol (Koo et al 2003), walkmycin C (Eguchi et al 2011), and anthraquinones (Coenye et al 2007), have been shown to inhibit the growth of cariogenic bacteria, and even the development of caries, but few of these compounds target S. mutans biofilms. Therefore, there is an urgent need to identify new approaches capable of targeting cariogenic bacteria in the biofilm state.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The cytoplasmic WalK domains (with C-terminal His tag) of Gram-positive B. subtilis, S. aureus, E. faecalis, and S. mutans were expressed and purified as described previously using E. coli BL21 (DE3) containing pETYycG-tru (Okada et al, 2010), pYycGSa (Watanabe et al, 2003), pETEfWalK (Watanabe et al, 2012), and pETSMVicK31-450 (Eguchi et al, 2011), respectively. The WalK cytoplasmic domains were preincubated in a kinase buffer {50 mM Tris-HCl (pH 8.5), 100 mM KCl, 100 mM NH 4 Cl, 5 mM MgCl 2 } at 30°C, as previously reported (Eguchi et al, 2011;Okada et al, 2007Okada et al, , 2010Watanabe et al, 2003). Waldiomycin was then added.…”
Section: Methodsmentioning
confidence: 99%